About Integration Advantages of Economic and Sociological Analysis of Institutional Changes - ШабановаМарина Андриановна (Journal of Economic Sociology, 2010)
The purpose of the paper is to provide basics for some opportunities and advantages of integration of some elements of sociological approach into economic analysis when we study institutional changes without taking the method of economics as a rule of thumb. The author does not want to cover all the interaction points as it is too wide. At the same time the author tries to show the crossings of economics and sociology may have constructive dialog for the analysis of institutional changes.